2002
DOI: 10.1677/joe.0.1720021
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a new monoclonal antibody to mammalian aromatase

Abstract: The biosynthesis of oestrogens from androgens is catalysed by the aromatase complex, an essential component of which is the aromatase cytochrome P450 (P450 arom) protein. Expression of a functional P450 arom is essential for normal fertility in males and females and the sequence of the protein is highly conserved. We have raised a new monoclonal antibody against a conserved peptide and validated it on fixed tissue sections of the rat, common marmoset (Callthrix jacchus) and human. The monoclonal antibody was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
75
1
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(89 citation statements)
references
References 51 publications
(56 reference statements)
11
75
1
2
Order By: Relevance
“…However, recently, aromatase has also been immunolocalised to the cytoplasm surrounding elongated spermatids (Turner et al 2002), and we and others have reported the presence of aromatase in human ejaculated spermatozoa (Aquila et al 2002, Lambard et al 2003.…”
Section: Introductionmentioning
confidence: 65%
“…However, recently, aromatase has also been immunolocalised to the cytoplasm surrounding elongated spermatids (Turner et al 2002), and we and others have reported the presence of aromatase in human ejaculated spermatozoa (Aquila et al 2002, Lambard et al 2003.…”
Section: Introductionmentioning
confidence: 65%
“…Laser microdissection of preantral and antral follicles has recently confirmed these results [20]. Within the granulosa cell layer of antral follicles, aromatase expression is highest in the mural granulosa cells at the outer edge of the follicle when compared to granulosa cells closest to the antral cavity [14,21]. Moreover, aromatase is not expressed in cumulus granulosa cells [14,21].…”
Section: Mature Ovariesmentioning
confidence: 85%
“…Within the granulosa cell layer of antral follicles, aromatase expression is highest in the mural granulosa cells at the outer edge of the follicle when compared to granulosa cells closest to the antral cavity [14,21]. Moreover, aromatase is not expressed in cumulus granulosa cells [14,21]. The marked compartmentalization of aromatase expression within the granulosa layer is particularly striking in mature follicles from rats at proestrus (Fig.…”
Section: Mature Ovariesmentioning
confidence: 91%
“…Antisera produced in rabbits against recombinant bovine P450c17 (Peterson et al 2001) and recombinant human P450arom (Conley et al 1996) served as primary antibodies. Additionally, a murine monoclonal antibody against a synthetic peptide corresponding to amino acids 376-390 of human P450arom (Turner et al 2002) was tested (clone H4, purchased from Serotec GmbH, Dü sseldorf, Germany); the peptide sequence used for immunisation is completely conserved in bovine P450arom. Serum from a non-immunised rabbit or dilution buffer were used as negative controls.…”
Section: Immunohistochemical Staining Proceduresmentioning
confidence: 99%